2022
DOI: 10.3390/app12157945
|View full text |Cite
|
Sign up to set email alerts
|

End-Effectors Developed for Citrus and Other Spherical Crops

Abstract: Citrus harvesting is time-intensive and labor-intensive, relying mainly on manual harvesting. The automatic harvesting of fruit and vegetable crops can not only reduce the physical labor of fruit farmers in the harsh field environment but also greatly improve the harvesting efficiency. Based on the principle of manual citrus picking, an end-effector with three-finger grasping is designed in this study. First, the structure of the end-effector was designed to achieve the function of stable grasping and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The results show that the flexible gripper is capable of the non-destructive grasping of tomatoes with a diameter between 65 and 95 mm, and can withstand a tensile force of 7 N, with a load of more than twice its own weight. Xiao et al [ 15 ] designed a fin-shaped flexible three finger grasping end-effector, as shown in Figure 6 . Its structure mainly includes: 1. connecting chuck, 2. fixed bracket, 3. clamping fingertip, 4. moving linkage, 5. stepping motor, 6. blade fixed frame, 7. cutting blade, and 8. clamping finger.…”
Section: Research Progress Of Fruit Vegetable and Meat Grippersmentioning
confidence: 99%
“…The results show that the flexible gripper is capable of the non-destructive grasping of tomatoes with a diameter between 65 and 95 mm, and can withstand a tensile force of 7 N, with a load of more than twice its own weight. Xiao et al [ 15 ] designed a fin-shaped flexible three finger grasping end-effector, as shown in Figure 6 . Its structure mainly includes: 1. connecting chuck, 2. fixed bracket, 3. clamping fingertip, 4. moving linkage, 5. stepping motor, 6. blade fixed frame, 7. cutting blade, and 8. clamping finger.…”
Section: Research Progress Of Fruit Vegetable and Meat Grippersmentioning
confidence: 99%
“…Researchers categorize the end-effector grippers into four major types: negative pressure adsorption end-effectors; shearing-style end-effectors; negative pressure adsorption end-effectors; cavity retrieval end-effectors; and flexible grasping end-effectors. [10,[34][35][36][37][38][39][40][41][42][43][44][45]. The selection of an appropriate end-effector gripper is determined by the physical characteristics of the fruits, such as their types, sizes, and the hardness of their peels.…”
Section: Introductionmentioning
confidence: 99%